Oxidative β-Halogenation of Alcohols: A Concise and Diastereoselective Approach to Halohydrins - Ai, Lingsheng; Wang, Weijin; Wei, Jialiang; Li, Qing; Song, Song; Jiao, Ning (Synlett, 2019)
β-Halohydrins bearing transformable halo- and hydroxyl groups, are easily converted into various valuable blocks in organic and pharmaceutical synthesis. A diastereoselective β-halogenation of benzylic alcohols was achieved under simple and low-cost conditions, which provided a direct synthesis of β-halohydrins. The simple reaction conditions, easily available reagents, high diastereoselectivities, and additional oxidant-free make this reaction very attractive and practical.
Keywords: halogenation; alcohols; dimethyl sulfoxide; halohydrins; oxidation